THE ROLE OF INFORMATION TECHNOLOGY IN EDUCATION WORLD (PERAN TEKNOLOGI INFORMASI DALAM BIDANG PENDIDIKAN; E-EDUCATION) - U. Abdullah Mumin (al-Afkar, Journal For Islamic Studies, 2019)
This research aims to explore the importance of information technology in the field of education. As an instrument of the modern digital world, the existence of information technology is possible to answer the level of learning difficulties that are currently considered conventional. This study uses a qualitative approach to the study of literature. As a result of this research, the influences of globalization, future education will be more open and two-way, diverse, multidisciplinary, and related to work productivity. With the development of information technology in the field of education, it is now possible to hold distance learning by using internet media to connect students with their lecturers, view student grades online, check finances, view class schedules, send assignments files given by lecturers etc. Penelitian ini bertujuan mengungkap pentingnya tekhnologi informasi dalam bidang pendidikan. Sebagai instrumen dunia digital modern, keberadaan teknologi informasi dimungkinkan dapat menjawab tingkat kesulitan pembelajaran yang saat ini dirasa masih konvensional. Penelitian ini menggunakan pendekatan kualitatif pendekatan kajian studi literatur. Dihasilkan dari penelitian ini, masuknya pengaruh globalisasi, pendidikan masa mendatang akan lebih bersifat terbuka dan dua arah, beragam, multidisipliner, serta terkait pada produktivitas kerja. Dengan adanya perkembangan teknologi informasi dalam bidang pendidikan, maka pada saat ini sudah dimungkinkan untuk diadakan belajar jarak jauh dengan menggunakan media internet untuk menghubungkan antara mahasiswa dengan dosennya, melihat nilai mahasiswa secara online, mengecek keuangan, melihat jadwal kuliah, mengirimkan berkas tugas yang diberikan dosen dan sebagainya.